2021
DOI: 10.1111/ecc.13491
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of mandala drawing in reducing psychological symptoms, anxiety and depression in hospitalised adolescents with cancer: A randomised controlled trial

Abstract: Objective: This study aimed to evaluate the effectiveness of individual mandala drawing methods on psychological symptoms, anxiety and depression in hospitalised adolescents with cancer.Methods: A randomised controlled trial design with repeated measures was conducted. The study was carried out in a paediatric haematology and oncology clinic in Turkey. The study protocol is registered at ClinicalTrials.gov NCT04297982. The study sample consisted of 60 hospitalised adolescents aged between 12 and 17.Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
(44 reference statements)
2
23
0
Order By: Relevance
“…The sample size in these studies varied between 5 and 83 children in each study; in one study alone, the sample size was 5 children (on the drawing),[ 25 ] in one study, the sample size was 16 children (music therapy),[ 26 ] but the sample size in 11 studies was between 20 and 60 people,[ 27 28 29 30 31 32 33 34 35 36 37 ] and the sample size was more than 60 people in four studies. [ 38 39 40 41 ]…”
Section: Resultsmentioning
confidence: 99%
“…The sample size in these studies varied between 5 and 83 children in each study; in one study alone, the sample size was 5 children (on the drawing),[ 25 ] in one study, the sample size was 16 children (music therapy),[ 26 ] but the sample size in 11 studies was between 20 and 60 people,[ 27 28 29 30 31 32 33 34 35 36 37 ] and the sample size was more than 60 people in four studies. [ 38 39 40 41 ]…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the results of existing studies, Kaimal et al 24 implemented a 45‐min‐long coloring session in a unique studio for 25 healthcare workers and 9 caregivers of cancer patients in an oncology unit and showed a significant decrease in the anxiety levels of healthcare workers and caregivers compared to the pre‐intervention period. In addition, when coloring therapy was administered to college students with anxiety disorders, 11,25 community‐dwelling elderly, 26 patients attending the emergency department, 23 women in late pregnancy, 27 and cancer patients, 28,29 the results showed some reduction in anxiety in this population compared to the pre‐intervention period. This study used GAD patients as subjects to confirm the anxiety‐relieving effect of coloring therapy and to broaden the scope of diseases treated with coloring therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of paediatric oncology patients and other groups show that a variety of methods ensured reductions in the anxiety of children. These include music therapy (Nguyen et al, 2010); virtual games (Gershonph et al, 2004); music books, balloons and videos (Kazak et al, 1996); drawing and writing techniques (Driessnack, 2006; Franck et al, 2008); mandala (Campenni & Hartman, 2020; Gürcan & Atay Turan, 2021; Stinley et al, 2015); and drawing and telling stories (Altay et al, 2017). Lopez‐Rodriguez et al (2020) showed that virtual reality, mobile applications and video games were beneficial to reduce anxiety among children with cancer.…”
Section: Discussionmentioning
confidence: 99%